PERILAKU PENCARIAN INFORMASI DIGITAL NATIVE IAIN SURAKARTA (STUDI TERHADAP PEMUSTAKA FAKULTAS USHULUDDIN DAN DAKWAH) - Khoirul Maslahah (Ikatan Pustakawan Indonesia, 2019)
This research was conducted to find out how to digitally natively in finding information to fulfill their duties. The results of this study will provide a discourse for librarians to understand the character of users and to improve the quality of excellent service. The approach uses the Ellis, Cox and Hall information behavior model. This research use desciptive qualitative approach. The results of this study indicate that respondents prefer to go straight to the shelf without looking at the catalog first, using the internet as a companion information source. Respondents use the internet as a means to seek entertainment and social networking. The second respondent in the search for information on the use of the internet as an information source is more dominant than the library.